Blood Pressure After Endovascular Thrombectomy and Malignant Cerebral Edema in Large Vessel Occlusion Stroke - Huang, Xianjun; Xu, Junfeng; Yang, Ke; Xu, Youqing; Yuan, Lili; Cai, Qiankun; Xu, Xiangjun; Yang, Qian; Zhou, Zhiming; Zhu, Shuanggen; Liu, Xinfeng (Frontiers in Neurology, 2021)
Background: Elevated blood pressure (BP) can cause blood–brain barrier disruption and facilitates brain edema formation. We aimed to investigate the association of BP level after thrombectomy with the development of malignant cerebral edema (MCE) in patients treated with endovascular thrombectomy (EVT). Methods: Consecutive patients who underwent EVT for an anterior circulation ischemic stroke were enrolled from three comprehensive stroke centers. BP was measured hourly during the first 24 h after thrombectomy. MCE was defined as swelling causing a midline shift on the follow-up imaging within 5 days after EVT. Associations of various BP parameters, including mean BP, maximum BP (BPmax), and BP variability (BPV), with the development of MCE were analyzed. Results: Of the 498 patients (mean age 66.9 ± 11.7 years, male 58.2%), 97 (19.5%) patients developed MCE. Elevated mean systolic BP (SBP) (OR, 1.035; 95% CI, 1.006–1.065; P = 0.017) was associated with a higher likelihood of MCE. The best SBPmax threshold that predicted the development of MCE was 165 mmHg. Additionally, increases in BPV, as evaluated by SBP standard deviation (OR, 1.061; 95% CI, 1.003–1.123; P = 0.039), were associated with higher likelihood of MCE. Interpretation: Elevated mean SBP and BPV were associated with a higher likelihood of MCE. Having a SBPmax > 165 mm Hg was the best threshold to discriminate the development of MCE. These results suggest that continuous BP monitoring after EVT could be used as a non-invasive predictor for clinical deterioration due to MCE. Randomized clinical studies are warranted to address BP goal after thrombectomy.